2020
DOI: 10.3354/aei00381
|View full text |Cite
|
Sign up to set email alerts
|

On the edge: assessing fish habitat use across the boundary between Pacific oyster aquaculture and eelgrass in Willapa Bay, Washington, USA

Abstract: Estuaries are subject to diverse anthropogenic stressors, such as shellfish aquaculture, which involve extensive use of estuarine tidelands. Pacific oyster Crassostrea gigas aquaculture is a century-old practice in US West Coast estuaries that contributes significantly to the regional culture and economy. Native eelgrass Zostera marina also commonly occurs in intertidal areas where oyster aquaculture is practiced. Eelgrass is federally protected in the USA as ‘essential fish habitat’, restricting aquaculture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…However, fish observations were higher for baskets than seagrass, perhaps reflecting the additional complex-ity that baskets add to the underlying habitat. Previous studies have likewise found similar invertebrate and fish communities between seagrasses and longline farms and between seagrasses and longlines with flipbag farms (Coe 2019, Muething et al 2020, Munsch et al 2021, although in some instances, long lines supported higher abundances but lower richness of fish than seagrass habitats (Dealteris et al 2004, Glenn 2016.…”
Section: Soldiers Pointmentioning
confidence: 69%
See 3 more Smart Citations
“…However, fish observations were higher for baskets than seagrass, perhaps reflecting the additional complex-ity that baskets add to the underlying habitat. Previous studies have likewise found similar invertebrate and fish communities between seagrasses and longline farms and between seagrasses and longlines with flipbag farms (Coe 2019, Muething et al 2020, Munsch et al 2021, although in some instances, long lines supported higher abundances but lower richness of fish than seagrass habitats (Dealteris et al 2004, Glenn 2016.…”
Section: Soldiers Pointmentioning
confidence: 69%
“…Mean (± SE) observations of bream as documented by 75 min remote underwater video deployments. Data are averaged across the 2 study years, as these did not significantly differ, with 4 cameras deployed on 3 replicate days of each season and year, to give n = 24. Letters above columns denote treatments that were significantly different (at α = 0.05) within each site and season by estimated marginal means structure can serve as important habitat to wild organisms, and there is growing evidence that off-bottom shellfish aquaculture can provide important fish habitat (Dealteris et al 2004, Mercaldo-Allen et al 2020, Muething et al 2020, Ferriss et al 2021) and trophic resources (Lefcheck et al 2019). Yet, uncertainty surrounding the impact of farm and infrastructure type on habitat provisioning functions remains a major knowledge gap which could inhibit the development of multifunctional shellfish aquaculture.…”
Section: Soldiers Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…It is comprised of the biofouling community found in the top 30 cm growing on floating objects and a subset of natural reef community members that enter bags as propaguels or small swimming juveniles. In Beaufort NC and around the globe in temperate and tropical harbors about 95% of biofouling organisms are invasive species, many of which arrived with boats and trade before or with the first European settlers [51][52][53] . Though found in the immediate coastal ocean [24] biofouling communities are particularly adapted to live in polluted harbors [54] .…”
Section: Ecosystem In a Bagmentioning
confidence: 99%